Micropropagation of Costus speciosus (Koen.) Sm. Using Nodal Segment Culture - Kshetrimayum PUNYARANI; Jitendra G. SHARMA (Notulae Scientia Biologicae, 2010)
Nodal segments of Costus speciosus (Koen.) Sm. containing single axillary buds were cultured on Murashige and Skoog medium (MS medium) supplemented with plant growth regulators for inducing plantlets. For breaking of axillary bud dormancy, nodal segments were cultured on 40-70gl-1 sucrose or 1-13 M adenine sulphate (AdS) supplemented MS basal medium containing 5 M 6-benzylaminopurine (BAP) and 1M ?-naphthalene acetic acid (NAA). The nodal segments cultured on 1-13 M AdS, 5 M BAP, 1 M NAA and 50gl-1 sucrose showed simultaneous production of shoots and roots while those cultured on 5 M BAP, 1 M NAA and 40-70gl-1 sucrose produced shoots only. The most effective media for breaking axillary bud dormancy was 5 M BAP, 1 M NAA, 50 gl-1 sucrose and 10 M AdS supplemented medium. The propagules from 40-70gl-1 sucrose produced roots in shoot multiplication medium, i.e.,10 M AdS, 1 M NAA, 50gl-1 sucrose and 3-11 M BAP supplemented medium. The best response for shoot multiplication was on 10 M AdS, 1 M NAA, 50gl-1 sucrose and 7 M BAP. The well-rooted shoots were hardened and transferred to the soil where they showed 95% survival rate. Results show that axillary bud can be used for micropropagation of Costus speciosus.